Filosofar en nuestra época. Una invitación para pensar la situación espiritual de nuestra época (2021)
Considering, on the one hand, that humanity is going through a spiritually overwhelming situation, without detriment to its material hardship, and, on the other hand, that philosophy, by the wisdom that distinguishes it, has the special responsibility to help in the search for answers, this article advocates a philosophy that assumes the challenge of thinking from the contradictory times we live in, trying to open horizons of hope that encourage the improvement of the world and its people.